Development of Alginate Extraction Method from Seaweed Turbinaria ornata - Rani Laksanawati; U. Ustadi; Amir Husni (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
Indonesia has a lot of high potential seaweed as a source of an alginate, but the extraction method had been used was not suitable. The aim of this research is to develop alginate extraction method from Turbinaria ornata seaweed with calcium method and compare the cost of extraction with an acid method as a control. In this research, various concentration of calcium chloride (CaCl2) was used in the separation of alginate from the extracted filtrate. The concentration of CaCl2 used varies from 0.50; 0.75; 1.00; 1.25; and 1.50 M. For comparison, alginate extraction with acid (control) method was used. Alginate quality parameters observed included alginate yield, product color degree, and gel viscosity. The results showed that the yield of alginate produced by calcium method was 36.89; 44.00; 56.00; 52.89 and 53.11% and for control 22.45%. From the degree of product color, CaCl2 concentration did not significantly affect the color of alginate but was darker when compared to the product extracted by the acid method. The viscosity of alginate produced by calcium method was 27,69; 26,57; 24.50; 22.41 and 19.92 cP while for control 32.88 cP. The extraction of Na-alginate with calcium method can decrease the need for Na-alginate extraction cost by 85% from the amount of  Na-alginate extraction cost requirement by the acid method.